Analysis of power law fluid-structure interaction in an open trapezoidal cavity. (15th May 2020) - Yaseen, Duna T.; Ismael, Muneer A.
Highlights: Power-law fluid structure interaction (FSI) and mixed convection is studied. The physical domain is an open trapezoidal cavity with a dangled elastic fin. Finite element method in Arbitrary Lagrangian-Eularian (ALE) is used. Fluttering phenomenon of the fin takes place with shear-thinning and Newtonian fluids. The stiffer fin experiences little deflection and hence larger wake region behind it. Abstract: The present paper investigates the mixed convection heat transfer of non-Newtonian fluid-structure interaction (FSI) inside an open trapezoidal cavity. The base of the cavity is fixed at constant temperature while the other walls are adiabatic. The flow passes over the open side of the cavity through a parallel-plate channel. An elastic fin is dangled from the top wall of the channel and stand facing the open cavity. The current model presents a two- dimensional incompressible laminar flow and unsteady-state conditions using the non-Newtonian power- law fluids. Numerical simulation is achieved using finite element method with arbitrary Lagrangian–Eulerian (ALE) scheme. The effects of Cauchy number, Reynolds number, Richardson number and the index of power law fluid are examined with ranges of (Ca = 10 −20 –10 −3, Re  = 100–300, Ri = 0.01–10 and n  = 0.5–1.5). The results show that at Re  = 300, Nusselt number of a stiff fin is 2.6% and 7% higher than that of softer flexible fin for n  = 0.5 and 1.5, respectively. For low Ri number, shear-thickening fluid manifests higher Nusselt number while for high Ri number, the shear-thinning fluid has the higher values. It is found also that the fluttering phenomenon of the fin takes place at the highest Ri and Re numbers with shear-thinning fluid and Newtonian fluid as well.